The Role of Médecins Sans Frontières (MSF) in Sea Rescue Operations in the Mediterranean: Legal Challenges and International Obligations - Zreik, Mohamad; Haron, Nazatul Faizah (Brawijaya Law Journal, 2025)
Since 2015, Médecins Sans Frontières (MSF) has played a crucial role in conducting search-and-rescue operations in the Mediterranean Sea, rescuing migrants and refugees fleeing conflict, poverty, and persecution in regions like North Africa and the Middle East. MSF’s humanitarian missions, aimed at saving lives, have often been met with criticism and legal challenges from European authorities, who accuse NGOs of encouraging illegal migration. This paper examines the legal complexities surrounding MSF's sea rescue operations, focusing on the tension between humanitarian obligations and state sovereignty. The analysis includes a review of international law of the sea, the principle of non-refoulement under the 1951 Refugee Convention, human rights law, and European Union migration and asylum regulations. By analyzing MSF’s legal battles, this paper explores the intersection of humanitarian action and state control over borders, illustrating the moral and legal dilemmas posed by these missions.